Every body : a celebration of diverse abilities - Rotner, Shelley (Holiday House, 2023)
Everybody has a body, and each body is different. Sometimes the differences mean certain kids have challenges. In this book you can meet some kids who face challenges and find out about their differences--as well as all the things everybody has in common.